The Students’ Senior High School Experiences in Poetry Reading Activities Assisted Vocabulary Learning: Narrative Inquiry - Siti Rohmah; Muhammad Reza Pahlevi; Abdul Kodir Al Baekani (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2021)
Teaching and learning vocabulary through poetry as a part of literature is not emphasized and focused to the students as an important part of language learning. To fill the gap, there are three findings of this study to find out how the students experiences in learning vocabulary through reading poetry activities. (1) The students lead to explore poetry in term of vocabulary enthusiastically. (2) Poetry as friendly use media in learning vocabulary. (3) The poetry serves a joyful learning experience while it challenges students to learn more. Narrative inquiry shows about the students’ story and experiences in learning through autobiographies, document of life, life stories, and histories. The data were collected through questionnaire and interview. The interview used semi structured interview with four students in second grade at SMAN 1 Cikarang Selatan as participants to give their experiences in learning by reading poetry activities in vocabulary leaning. To strengthen the interview data, there was used items of questionnaire included ten points that shown about how the students experiences in poetry assisted vocabulary learning through reading poetry activities. The questionnaire gathered from 46 students that like poetry and English lesson in the same school above